Analisis Potensi Air Tanah Menggunakan Metode Geolistrik Konfigurasi Schlumberger pada Kawasan Rawan Kekeringan Desa Wanadri Kecamatan Bawang Kabupaten Banjarnegara - Rausyanfikr, Hamas; Setyaningsih, Wahyu; Setyowati, Dewi Liesnoor (Geo-Image, 2019)
The research objective is to analyze the drought conditions in the Wanadri village, calculate and analyze the potential of groundwater in the Wanadri village using Configuration Geolistrik Schlumberger and analyze the balance of water needs with the availability of groundwater in the Wanadri village. This research used Balance Studies research methods. Namely to calculate and compare the domestic water requirement for the population and the availability of existing groundwater at Wanadri village. The results showed that the occurrence of drought in the village of Wanadri factors is the geological conditions and low rainfall. Wanadri villages are on formation member of Breksi, Grewake, and Ulo Lok Complex. The conditions resulted in Wanadri village does not have many aquifers. The availability of groundwater contained in Wanadri village is 4.356.301,59 m3/year or 4.356.301.590 liters. While, the domestic water needs in 2015, 2018, 2021, 2024, 2027 and 2030 amounted to 88.590.945,8 m3 90.871.334,4 m3, 93.216.262,3 m3, 95.604.216,4 m3, 98.056.709,8 m3 and 100.573.742,5 m3. The figure shows that the availability of groundwater is large enough to meet all the water needs of the Wanadri villagers until 2030.